KEKOSONGAN HUKUM PADA PENYIARAN DI MEDIA SOSIAL - Moh Yusuf (TADULAKO MASTER LAW JOURNAL, 2024)
The aim of the research is to find out and examine the urgency of regulating broadcasting on social media in Indonesia and to find out and examine the legal consequences of the void of broadcasting law on social media. The research method used is a normative method. The research results show that broadcasting activities carried out through individual or community social media platforms have not been regulated in broadcasting regulations, so that broadcasting via social media platforms does not have legal standing in statutory regulations, in particular Law no. 32 of 2002 concerning Broadcasting, social media cannot be called press even though social media platforms carry out journalistic activities. The existence of a legal vacuum gives rise to legal uncertainty which will result in legal chaos, if it is linked to the legal theory of development, namely the formation of laws/legal regulations in the form of written regulations and the legal consequences of the legal vacuum of broadcasting in social media, namely that broadcasters are not subjects or objects and is not part of the broadcasting regulations as regulated in Law no. 32 of 2002 concerning Broadcasting, which can result in uncontrolled broadcasting carried out via social media platforms because there is no supervision, violations of broadcasting are only related to Law no. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Information and Electronic Transactions. Abstrak Tujuan Penelitian untuk mengetahui dan mengkaji urgensi pengaturan penyiaran dalam media sosial di Indonesia dan untuk mengetahui dan mengkaji akibat hukum terjadinya kekosongan hukum penyiaran dalam media sosial. Metode Penelitian yang digunakan adalah metode normatif. Hasil penelitian menunjukan kegiatan penyiaran yang dilakukan melalui platform media sosial perorangan atau masyarakat belum diatur dalam peraturan-peraturan penyiaran, sehingga penyiaran melalui platform media sosial tidak memiliki kedudukan hukum dalam peraturan perundangan pada khususnya UU No. 32 Tahun 2002 tentang Penyiaran, media sosial tidak dapat disebut sebagai pers meskipun platform media sosial melakukan kegiatan jurnalistik. Adanya kekosongan hukum menimbulkan ketidakpastian hukum akan berakibat pada kekacauan hukum, apabila dikaitkan dengan teori hukum pembangunan yaitu dengan adanya pembentukan hukum/regulasi hukum berupa peraturan yang bersifat tertulis dan Akibat hukum terjadinya kekosongan hukum penyiaran dalam media sosial yaitu pelaku penyiaran bukanlah sebagai subjek atau objek dan tidak menjadi bagian dari pengaturan penyiaran sebagaimana diatur dalam UU No. 32 Tahun 2002 tentang Penyiaran, sehingga dapat mengakibatkan tidak terkontrolnya penyiaran yang dilakukan melalui platform media sosial karena tidak ada pengawasan, pelanggaran terhadap penyiaran hanya berkaitan dengan UU No. 19 Tahun 2016 tentang Perubahan Atas UU No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik